Comparison of long-term complications in cancer patients with incidental and acute symptomatic venous thromboembolism - Barca-Hernando, María; Lopez-Ruz, Sergio; Marin-Romero, Samira; Elias-Hernandez, Teresa; Otero-Candelera, Remedios; Jara-Palomares, Luis (Frontiers in Cardiovascular Medicine, 2023)
Background Clinical practice guidelines recommend that patients with incidental venous thromboembolism (VTE) receive the same anticoagulant therapy as those with symptomatic VTE. We aimed to compare the rate of complications between cancer patients with incidental and symptomatic VTE through a long-term follow-up cohort. Methods We performed a post hoc analysis of prospective studies of cancer patients with VTE between 2008 and 2019, with the primary outcome of rates of recurrent VTE and clinically relevant bleeding (CRB) in incidental and symptomatic VTE groups. Results In total, 796 patients were included, of which 42.8% had incidental VTE. No significant differences were noted in the rate of recurrent VTE (0.4 per 100 patients/month vs. 0.5 per 100 patients/month; p = 0.313) and in the rate of CRB (0.6 per 100 patients/month vs. 0.5 per 100 patients/month; p = 0.128) between patients with incidental VTE and symptomatic VTE, respectively. At six-month follow-ups, the cumulative incidence of CRB was significantly higher in patients with incidental VTE than that in those with symptomatic VTE (7.9% vs. 4.4%, respectively; OR: 1.8; 95% CI: 1.01–3.2). Conclusion Cancer patients with incidental VTE had similar rates of CRB and VTE recurrence in long-term follow-up compared with patients with symptomatic VTE. At six-month follow-ups, patients with incidental VTE had a higher cumulative incidence of CRB than those with symptomatic VTE.